Post-immigration factors affecting retention in HIV care and viral suppression in Latin American and Caribbean immigrant populations in the United States: a systematic review. Issue 8 (17th November 2022) - Ramírez-Ortiz, Daisy; Seitchick, Jessica; Polpitiya, Medhani; Algarin, Angel B.; Sheehan, Diana M.; Fennie, Kristopher; Cyrus, Elena; Trepka, Mary Jo
ABSTRACT: Objectives: To reduce disparities in HIV care outcomes among Latin American and Caribbean (LAC) immigrants living with HIV in the U.S., it is necessary to identify factors influencing HIV care in this population. A systematic review that provides a comprehensive understanding of factors influencing retention in HIV care and viral suppression among LAC immigrants living with HIV in the U.S. is lacking. This systematic review used the Immigrant Health Services Utilization theoretical framework to provide an understanding of these factors. Design: We searched for peer-reviewed publications in MEDLINE, EMBASE, CINAHL, PsycINFO, and ASSIA, from January 1996 to June 2020. Results: A total of 17 qualitative ( n = 10) and quantitative ( n = 7) studies were included in the review. The most commonly reported general and immigrant-specific factors appearing in studies were undocumented immigration status, HIV stigma, homophobia, cultural norms, values and beliefs, family and social support, language barriers, structure, complexity and quality of the U.S. healthcare delivery system, and patient-provider relationship. Conclusion: These findings highlight the importance of considering immigrant-specific factors along with general factors to improve the provision of HIV care services and HIV care outcomes among LAC immigrant populations.